Ultrahigh strain-rate bending of copper nanopillars with laser-generated shock waves (2013)
ABSTRACT: An experimental study to bend FIB-prepared cantilevered single crystal Cu nanopillars of several hundred nanometers in diameter and length at ultrahigh strain rate is presented. The deformation is induced by laser-generated stress waves, resulting in local strain rates exceeding 107 s 1. Loading of nano-scale Cu structures at these extremely short loading times shows unique deformation characteristics. At a nominal stress value of 297 MPa, TEM examination along with selected area electron diffraction characterization revealed that twins within the unshocked Cu pillars interacted with dislocations that nucleated from free surfaces of the pillars to form new subgrain boundaries. MD simulation results were found to be consistent with the very low values of the stress required for dislocation activation and nucleation because of the extremely high surface area to volume ratio of the nanopillars. Specifically, simulations show that the stress required to nucleate dislocations at these ultrahigh strain rates is about one order of magnitude smaller than typical values required for homogeneous nucleation of dislocation loops in bulk copper single crystals under quasi-static conditions.